FUNCTIONAL AND NUTRITIONAL COMPOSITION OF ACTIVATED CHARCOAL OF Terminalia Catappa (FUDMA JOURNAL OF SCIENCES, 2024)
Terminalia catappa (T. catappa) is a folklore plant whose leaves, roots and stem bark treat various infectious diseases such as dermatosis and hepatitis. However, herbalists often transform some parts, like the stem, via pyrolysis to charcoal to achieve a different therapeutic outcome. Charcoal has been known as an anti-poisonous substance with no therapeutic or nutritional relevance. This study transformed the stem bark of T. catappa to charcoal, evaluated its proximate minerals and phytochemical compounds using standard methods, including inductive coupled plasma atomic emission spectroscopy (ICP AES) and Gas chromatography-mass spectroscopy (GC-MS). Stem bark were gotten from tree, dried in the sun, and then subjected to a Thermofitcher muffle furnace at 1450 °C without oxygen for about an hour to activated charcoal.Subsequently. The charcoal was pulverised to smooth powder and then subjected to analysis. Proximate analysis reveals that T catappa charcoal is rich in primary nutrients such as carbohydrates (65.20±4.34), proteins (5.68±0.21), crude fibre (8.31±1.10), ash (13.20±2.10) and moisture content (7.50±0.10) %. Mineral analysis of the extract revealed the presence of essential minerals such as calcium (128.26±11.09), copper (0.83±0.001), magnesium (77.80±9.08), iron (24.51±5.08), manganese (1.83±0.05), and zinc (4.59±0.12) mg/100g as the most predominant, which are crucial for numerous cellular processes. Two (2) phytochemical compounds were detected by GC-MS, including methyl-6-0 beta-galatose (93.24%) and stigmastan-3, 5-diene (6.76 %). The study revealed that charcoal is contains nutrients and functional compounds that may be included in feed and a potential therapeutic drug target against hypercholesterol and cancer.
Keywords: Terminalia ivorensis; ICP-AES; Hypercholesterol; Cancer; Proximate